Clifford, the big red dog - Bridwell, Norman (New York : Scholastic, 2002)
Emily Elizabeth describes the activities she enjoys with her very big, very red dog and how they take care of each other.
"Deluxe anniversary edition"--Jkt.
360L
Decoding demand: 29 (low) Semantic demand: 40 (low) Syntactic demand: 39 (low) Structure demand: 75 (high)
Accelerated Reader
Accelerated Reader AR
Keywords: Dogs -- Juvenile fiction; Clifford (Fictitious character : Bridwell) -- Juvenile fiction